Indian critiques of Gandhi - Coward, Harold G. (Albany : State University of New York Press, 2003)
Annotation. A volume in the SUNY series in Religious Studies Harold Coward, editor.
The convergence of distinct worlds : Nehru and Gandhi / Robert D. Baird -- Gandhi, Ambedkar, and untouchability / Harold Coward -- Of many Mahatmas : Besant, Gandhi, and Indian nationalism / Joy Dixon -- Sri Aurobindo's dismissal of Gandhi and his nonviolence / Robert N. Minor -- Tagore and Gandhi / T.S. Rukmani -- The Hindu Mahasabha and Gandhi / Ronald Neufeldt -- Gandhi and the Christian community / Timothy Gorringe -- The Mathatma and the Sikhs / Nikky-Guninder Kaur Singh -- Indian Muslim critiques of Gandhi / Roland E. Miller -- Gandhi and the Hindi-Urdu question / Daud Rahbar -- Conclusion : A debate for our times / Julius Lipner -- Appendix : Chronology of Gandhi, his critics, and the independence movement / Hussein Keshani.
Includes index.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Political and social views; Gandhi, -- Mahatma, -- 1869-1948; Gandhi, Mohandas Karamchand, -- (1869-1948) -- Pensée politique et sociale; Gandhi, Mohandas Karamchand; India -- History -- Autonomy and independence movements; India -- Politics and government -- 1919-1947.; Inde -- Politique et gouvernement -- 1919-1947.; HISTORY; Autonomy and independence movements; Political and social views; Politics and government; India; Indien; Onafhankelijkheidsbewegingen; Politieke ideeën.; Kritiek (algemeen); Inde -- Histoire -- Autonomie et mouvements indépendantistes.; Inde -- Politique et gouvernement -- 1919-1947.; 1919-1947; History